The Effect of the Light Property Box (Kosica) Media-Assisted Experimental Method on Students' Learning Outcomes in Science Learning at Grade IV of UPTD SD Negeri 122371 Pematangsiantar - Yohana Dwi Meilani Sihotang; Canni Loren Sianturi; Lisbet Novianti Sihombing (International Journal of Technology and Education Research, 2026)
This study aims to determine the effect of the Light Properties Box (Kosica) Media-Assisted Experimental Method on the science learning outcomes of fourth-grade students at the UPTD of Pematangsiantar State Elementary School 122371. This study employed a quantitative pre-experimental method with a One Group Pretest-Posttest design. The study population and sample size were 22 students. Data collection used a pretest and posttest, which had previously been tested for validity and reliability. Of the 50 questions tested, 30 were valid and suitable for use in the study. The reliability test results showed a value of 0.970, a high category, thus declaring the instrument consistent and reliable. The pretest was administered to determine students' initial abilities before the treatment, followed by the application of the Light Properties Box (Kosica) Media-Assisted Experimental Method to the topic of light properties. This method is designed to help students understand concepts concretely and increase student engagement during the learning process. After the treatment, students took a posttest to determine improvements in learning outcomes. The results showed that the average pretest score of 53.3 increased to 78.3 in the posttest. The N-Gain test obtained a score of 0.6525, which is in the moderate to high category, while the t-test results showed a calculated t value of 10.786, which is greater than the t table of 1.720. Thus, Ho is rejected and Ha is accepted. It can be concluded that the Experimental Method Assisted by the Light Properties Box (Kosica) Media has a significant effect on students' science learning outcomes.